1989
DOI: 10.4319/lo.1989.34.5.0913
|View full text |Cite
|
Sign up to set email alerts
|

Benthopelagic biomass distribution and oxygen consumption in a deep‐sea benthic boundary layer dominated by gelatinous organisms

Abstract: A quantitative plankton net sampler with a multicompartment cod-end for use with deep submersible vehicles was developed. This cod-end protects samples from surface temperatures so that deep-sea animals can be recovered alive. The DSV Alvin used it to sample the benthopelagic faunas forms, a group dominated by copepods and larger crustaceans, were more uniformly distributed and ranged from 2.1 to 7.9 mg wet wt m-3. Abundances of Scotoanassa sp., but not the other categories, varied greatly between years and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Alvariño (1967) reported that Haliscera bigelowi (as Homoeonema alba) and Aegina citrea were found only below 1000 meters. The narcomedusa Solmissus incisa was reported by Thuesen & Childress (1994) and Childress et al (1989, as Solmaris sp.) as another deep living species.…”
Section: Discussionmentioning
confidence: 97%
“…Alvariño (1967) reported that Haliscera bigelowi (as Homoeonema alba) and Aegina citrea were found only below 1000 meters. The narcomedusa Solmissus incisa was reported by Thuesen & Childress (1994) and Childress et al (1989, as Solmaris sp.) as another deep living species.…”
Section: Discussionmentioning
confidence: 97%
“…First, all 3 species are restricted 1984) in their distributions to the benthic boundary layer. This region of the water column is characterized by relatively high levels of available food (energy), in the form of particulate organic material, small crustaceans, and microorganisms, when compared with overlying midwater communities (Lampitt 1985, Walsh et al 1988, Childress et al 1989. In these regions of the water column, grazing rates and metabolic activities have been reported to be elevated in response to the higher particle concentrations (Smith 1982, Wishner & Meise-Munns 1984 Childress et al 1990).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Wishner and her colleagues have examined this fauna in some detail (Wishner 1980a, b, c, Wishner & Meise-Munns 1984, Gowing & Wishner 1986, Wishner & Gowing 1987. They refer to this environment as the benthopelagic or benthic boundary layer, as do Childress et al (1989). It has its own endemic fauna, phylogenetic aspects of which have been partially examined (Grice & Hulsemann 1970, Grice 1972, Wishner 1980c, Hargreaves 1984, Domanski 1986, Gowing & Wishner 1986, Childress et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…They refer to this environment as the benthopelagic or benthic boundary layer, as do Childress et al (1989). It has its own endemic fauna, phylogenetic aspects of which have been partially examined (Grice & Hulsemann 1970, Grice 1972, Wishner 1980c, Hargreaves 1984, Domanski 1986, Gowing & Wishner 1986, Childress et al 1989. These studies are linked to those of benthopelagic coupling reviewed by Angel (1984Angel ( , 1990, Deuser (1986) and Fowler & Knauer (1986).…”
Section: Introductionmentioning
confidence: 99%